Pengaruh Faktor Ekonomi dan Lingkungan terhadap Deforestasi di Indonesia - Elfrida Eka Ayuningtyas; Muhammad Akmal Fadhillah; Nathania, Vanisa Azra; Surya Puspita Sari; Magdalena Effendi (BPS Kalimantan Timur, 2025)
Indonesia is one of the countries with the highest rate of deforestation in the world, influenced by various economic and environmental factors. This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), forest area, population density, forest fires, and CO? emissions on deforestation in Indonesia during the 2018–2022 period using panel data regression analysis. Based on the Chow, Hausman, and Lagrange Multiplier tests, the Random Effects Model was identified as the most appropriate model to explain the relationships among variables. The results indicate that forest fires, forest area, and CO? emissions have a significant effect on deforestation, while GRDP and population density show no significant effect. Forest fires and CO? emissions positively influence deforestation, and forest area also shows a positive effect, indicating that provinces with larger forest coverage tend to record higher levels of deforestation. These findings suggest that environmental factors play a more dominant role than economic factors in determining the rate of deforestation in Indonesia.